2014
DOI: 10.1590/s1677-5538.ibju.2014.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for hyberbaric oxygen as primary treatment for grade IV radiation-induced haemorrhagic cystitis? a prospective pilot-feasibility study and review of literature

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: To examine the safety and efficacy of hyperbaric oxygen as the primary treatment for Grade IV radiation-induced haemorrhagic cystitis. Materials and Methods:Hyperbaric oxygen was prospectively applied as a primary treatment option in 11 patients with Grade IV radiation cystitis. Primary endpoint was the incidence of complete and partial response to treatment. Secondary endpoints included the duration of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…In these patients, HBO significantly reduced the further development of late irradiation injury. A similar conclusion was presented by Dellis et al [15], who proved that HBO therapy could be used not only as a treatment but also as a prevention in patients during and after pelvic radiation therapy. The authors concluded that HBO was safe both for the bladder structure and for patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In these patients, HBO significantly reduced the further development of late irradiation injury. A similar conclusion was presented by Dellis et al [15], who proved that HBO therapy could be used not only as a treatment but also as a prevention in patients during and after pelvic radiation therapy. The authors concluded that HBO was safe both for the bladder structure and for patients.…”
Section: Discussionsupporting
confidence: 80%
“…Intravenous infusion of MSC caused in some patients disappearance of symptoms with no adverse effects but further studies are needed to confirm their efficiency [14]. HBO was introduced to improve the clinical state after radiation of various organs, including the bladder [5,[15][16][17]. Sufficient HBO therapy was described in both adult and pediatric patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…HBO increases the bladder tissue oxygen tension, enhancing neovascularization and normal tissue growth with 80-92% improvement at 1 year and durable responses in more than 70% [42,43]. It should be considered before severe changes are established with greater benefit seen with younger age, treatment within 6 months of onset and higher radiation dose.…”
Section: Urinary Incontinence and Overactive Bladdermentioning
confidence: 99%
“…Overall rate of recurrence was 0.12/year. In a recent prospective study to define primary role of hyperbaric oxygen in radiation cystitis, 11 patients were treated with HBO (Dellis et al, 2014). Nine patients (81.8 %) and 3 patients (18.2%) had complete and partial response respectively.…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%